Chemical and morpho-functional aspects of the interaction between a Neotropical resin bug and a sticky plant - Jiménez-Pomárico, Alejandra (Universidad de Costa Rica, 2019)
Rubus adenotrichos is an Andean blackberry plant bearing glandular trichomes which secrete an adhesive exudate. The resin bug Heniartes stali is frequently found on this plant and collects this exudate using the forelegs to enhance its preying capacity. Here, we describe the morphology of the plant’s glandular trichomes with the aid of light and scanning electron microscopy, as well as the chemical components of the exudate by histochemical and gas chromatography-mass spectrometry analysis. We have also combined behavioral observations with the analysis of the insect leg morphology to identify possible morpho-functional adaptations evolved by H. stali for collecting the sticky secretions. Glandular trichomes exhibited a multicellular long stalk and a calyx-shaped head with radially aligned cells. The composition of the resinous fluid was mainly terpenes and phenolics, which may contribute to its sticky properties. Brush-like structures on the tibia of forelegs in H. stali suggests an adaptive trait for collecting the trichomes exudate. A profusely hair-covered area on metatibiae operated as a resin storage structure. Abundant pore-like openings were observed in the cuticle of this area through which substances could be conceivably secreted to prevent resin hardening. These findings combine morphological and chemical features of a fascinating insect-plant interaction in the Neotropics.